Identifikasi Jamur Penyebab Tinea Kapitis Pada Anak-Anak - Bedah, Sumiati; Oktiana, Denisa (Universitas Mohammad Husni Thamrin, 2024)
Indonesia is a tropical country with high humidity conditions which can create a good atmosphere for fungal growth. Therefore, fungal infections found in Indonesia are quite diverse, one of which is tinea capitis, an infection caused by dermatophyte fungi on the scalp and hair follicles. The most common causative agents are Tricophyton and Microsporum. Tinea capitis attacks pre-puberty children more often, this is thought to be because the sebaceous glands at pre-puberty are not yet perfect. Laboratory diagnosis of tinea capitis can be carried out using several methods, including microscopic examination with KOH as an initial screening test, fungal culture which is the gold standard, trichoscopy, and the use of a Wood's lamp. This research uses secondary data from a literature study conducted in previous research journals. Based on a review of research results from five related journals, 3 show that the fungal species Microsporum canis most often causes tinea capitis infections in children. Tinea capitis is more common in pre-pubertal children and males. Boys are more susceptible to tinea capitis infection than girls. From the results of this study, it can be concluded that Microsporum canis is the most dominant fungus that infects tinea capitis in pre-puberty children, especially boys. The most commonly used examination methods for tinea capitis are microscopic examination with KOH and fungal culture. Pre-puberty children are advised to always maintain personal hygiene, especially the scalp and hair. Keywords: Children, Microsporum canis, Tinea capitis